(untitled) (CIPEEX, 2023)
The anthropocentric view of human beings led a large part of the world’s population to behave as exceptional consumers towards other living beings. In an attempt to improve environmental standards and, above all, to raise awareness among humans about the orderly use of natural resources, it was noted that from these concerns, initiatives emerged aimed at solving environmental problems, such as the creation of protected areas. This text aims to reflect on the creation of protected areas from a perspective of the extent of these areas in Brazilian territory and in the state of Mato Grosso. Although it is possible to observe many advances in the processes of creating and managing protected areas in recent times, there are still many gaps to be filled, factors that can be minimized with the maintenance and expansion of monitoring and management systems.